Diagnostic Value of MRI in Placental Adhesive Disorders in Pregnancy - Sathyakumar, Kirthi; Chandramohan, Anuradha; Eapen, Anu; Abraham, Anuja (Journal of Gastrointestinal and Abdominal Radiology, 2023)
Background The spectrum of placental adhesive disorders (PAD) forms an important cause for emergency cesarean hysterectomy, requiring an accurate prenatal diagnosis for optimal obstetric management.Purpose The aim of this study was to assess the utility of magnetic resonance imaging (MRI) and to identify the individual MRI features that are most useful in the evaluation of PAD.Materials and Methods This was a retrospective review of the MRI of 24 women with abnormal placentation, confirmed using histopathology/intraoperative findings as the reference standard. Patients were categorized as negative or positive for PAD (placenta accreta, increta, and percreta) on MRI and compared with the reference standard. We assessed the diagnostic performance of MRI and the features that best correlated with the presence of PAD.Results Among the 24 women (mean age: 29.8 years) with risk factors, 16 had PAD (6 accreta, 7 increta, and 3 percreta). There was a history of previous lower segment cesarean section and placenta previa in 14 (87.5%). MRI could identify the presence of PAD in all (100% sensitivity) and its absence in three out of eight patients (37.5% specificity). The features with highest sensitivity were intraplacental dark bands (100%), myometrial thinning/loss of interface with myometrium (100%), placental heterogeneity (75%), and uterine contour abnormality (75%).Conclusion MRI is an important modality for the investigation of PAD in suspected cases, with excellent sensitivity and good accuracy. Identifying the presence of risk factors, low-signal-intensity bands, and thinning/loss of placental–myometrial interface will aid in its diagnosis.
Keywords: MRI; placenta accreta; placenta previa; abnormal placentation; pregnancy